Analisis SWOT dalam Membangun Strategi Pemasaran yang Efektif pada Tagify - Aisya Tyanafisya; Siti Farah Fakhirah; Asa Yuaziva; Wien Kuntari (Jurnal Transformasi Bisnis Digital, 2024)
This study aims to analyze the internal and external factors influencing the marketing strategy of Tagify, a business engaged in the design of lanyards and ID cards. Using a descriptive qualitative analysis method, the study collects secondary data from literature reviews related to marketing strategies and SWOT analysis. The findings reveal that Tagify's strengths lie in creative design, fast production capability, and flexibility in meeting customer demands. However, the main challenges are limited production capacity and suboptimal use of social media for marketing. Significant opportunities exist in the growing demand for custom products in corporate sectors and large events, while the primary threat comes from intense price competition. The implications of this research show that SWOT analysis is crucial in formulating effective marketing strategies to address challenges, seize available opportunities, and strengthen Tagify's competitive position in the market.